2019
DOI: 10.15421/021924
|View full text |Cite
|
Sign up to set email alerts
|

Morphobiological analysis of Trichuris vulpis (Nematoda, Trichuridae), obtained from domestic dogs

Abstract: The parasitic nematode Trichuris vulpis Frölich, 1789 is the pathogen of trichuriasis in domestic and wild carnivores, and humans. This helminth species is distributed world-wide in populations of domestic dog (Canis lupus familiaris). The prevalence of T. vulpis in dogs depends to a large degree on the morphofunctional and biological adaptations of the parasite which support its high survivability in various environmental conditions. The present study considers the species-specific peculiarities of morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
(55 reference statements)
0
11
2
1
Order By: Relevance
“…In conclusion, the authors, identified the parasite as T. serrata, but recommended that molecular studies must be done in order to reliably identify this parasite [31]. In dogs, male and female adult T. vulpis could be identified based on nine parameters (including body length, length of cuticular processes, and width of body at tail part) [32]. Male T. vulpis can be distinguished from other species by spicule sheath ornamentation (the dimensions of the spicule) [32].…”
Section: Trichuriasis Of Manmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the authors, identified the parasite as T. serrata, but recommended that molecular studies must be done in order to reliably identify this parasite [31]. In dogs, male and female adult T. vulpis could be identified based on nine parameters (including body length, length of cuticular processes, and width of body at tail part) [32]. Male T. vulpis can be distinguished from other species by spicule sheath ornamentation (the dimensions of the spicule) [32].…”
Section: Trichuriasis Of Manmentioning
confidence: 99%
“…In dogs, male and female adult T. vulpis could be identified based on nine parameters (including body length, length of cuticular processes, and width of body at tail part) [32]. Male T. vulpis can be distinguished from other species by spicule sheath ornamentation (the dimensions of the spicule) [32].…”
Section: Trichuriasis Of Manmentioning
confidence: 99%
“…For Ascaris and Trichuris , the incubation periods postexposure were based on published larval development times of each species: A. suum eggs are infectious 18 or more days after passage ( 16 ); Trichuris eggs are infectious within 15–30 days after passage, with T. vulpis eggs developing to an infectious state within 18 days in laboratory culture ( 32 ). The incubation protocol consisted of topping up wells with distilled water and stirring daily using a toothpick to ensure adequate oxygen diffusion and avoid desiccation.…”
Section: Methodsmentioning
confidence: 99%
“…Among the group of nematodes, the parasites of Trichuris are some of the most commonly found, occurring in various geographical regions and with climatic differences. This genus has around 80 species and can parasitize several animals in addition to humans [20].…”
Section: Introductionmentioning
confidence: 99%